Pediatric multiple sclerosis: current perspectives on health behaviors - Sikes EM; Motl RW; Ness JM (Dove Medical Press, 2018)
Elizabeth Morghen Sikes,1 Robert W Motl,1 Jayne M Ness2 1Department of Physical Therapy, University of Alabama at Birmingham, Birmingham, AL, USA; 2Department of Pediatric Neurology, University of Alabama at Birmingham, Birmingham, AL, USA Purpose: Pediatric-onset multiple sclerosis (POMS) accounts for ~5% of all multiple sclerosis cases, and has a prevalence of ~10,000 children in the USA. POMS is associated with a higher relapse rate, and results in irreversible disability on average 10 years earlier than adult-onset multiple sclerosis. Other manifestations of POMS include mental and physical fatigue, cognitive impairment, and depression. We believe that the health behaviors of physical activity, diet, and sleep may have potential benefits in POMS, and present a scoping review of the existing literature. Methods: We identified papers by searching three electronic databases (PubMed, GoogleScholar, and CINAHL). Search terms included: pediatric multiple sclerosis OR pediatric onset multiple sclerosis OR POMS AND health behavior OR physical activity OR sleep OR diet OR nutrition OR obesity. Papers were included in this review if they were published in English, referenced nutrition, diet, obesity, sleep, exercise, or physical activity, and included pediatric-onset multiple sclerosis as a primary population. Results: Twenty papers were identified via the literature search that addressed health-promoting behaviors in POMS, and 11, 8, and 3 papers focused on diet, activity, and sleep, respectively. Health-promoting behaviors were associated with markers of disease burden in POMS. Physical activity participation was associated with reduced relapse rate, disease burden, and sleep/rest fatigue symptoms. Nutritional factors, particularly vitamin D intake, may be associated with relapse rate. Obesity has been associated with increased risk of developing POMS. POMS is associated with better sleep hygiene, and this may benefit fatigue and quality of life. Discussion: Participation in health behaviors, particularly physical activity, diet, and sleep, may have benefits for POMS. Nevertheless, there are currently no interventions targeting promotion of these behaviors and examining the benefits of managing the primary and secondary manifestations of POMS. Keywords: POMS, health promotion, physical activity, diet, sleep